Teachers’ Challenges toward Chinese-Indonesian Students in ELT: A Multicultural Narrative Analysis - Qorihah, Dzul Kamalil; Hertiki, Hertiki (Indonesian Journal Publisher, 2024)
Javanese and Chinese-Indonesian ethnics are the majority and minority ethnic in Indonesia. Lots of difference are always found in their social environment including education. Teachers will face difficulties if they don’t understand well how to engage with multicultural students. Therefore, both ethnics require intercultural competence which is the composite of knowledge, attitude, skill and understanding adjusted through intercultural activities. This research aims at exploring the challenges of EFL teachers’ experiences with Javanese ethnicity on Chinese-Indonesian students in English Language Teaching. This study uses qualitative method with narrative approach. The data in this study are statements from interview session which is done by two EFL teachers from Javanese as subjects of data source. Then, the data are analysed by thematic. This study delivers three challenges as the result. First challenge comes from rich Chinese-Indonesian family. Secondly, split of mother language becomes a challenge. The last challenge is high work ethic from Chinese-Indonesian people.